PERLUASAN FRASE DALAM CERPEN DAGANG CANANG - Adi Upadana, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Linguistics is the study of language. Balinese is the language used by Balinese people to communicate. Language is also used in pouring a sense of human art such as making a literary work. This study examines the use of grammar in a literary work. The object of research is phrases. A phrase is a construction built by constituents with various categories or classes of words. There are many variations that will be formed in a phrase. As a research subject, we use a short story entitled Dagang Canang. Based on data analysis, the expansion of Balinese phrases in the short story Dagang Canang includes: Noun phrase to the left Conj+N+N, Adj+N, Adj+N+N, Adv+N+N. Noun phrases to the right N+Adverb, N+N+Adj, N+Num, N+Adj. The noun phrases to the left and right have the pattern Verb+N+Num. Verbal phrases to the left Conj+V, Adverb+V, N+V, Pronomia+V. Verbal phrases to the right V+N, V+Pronouns. Verbal phrases to the left and right N+Verb+Adverb.